Analytical study of Al-Hawi’s book, by Imam Abi Al-Hassan Ali bin Mohammed Al-Basri, Al-Mawardi Al-Shafei, 450 H [From the Book of Hunting and Carcasses to the Book of swearing] Model - Al-Zubaidi, Abdullah Ahmed (Journal of Islamic Sciences, 2023)
In his book Al-Hawi, the Mawardi Imam distinguished himself with a set of landmarks, which the researcher wanted to show to those involved in the industry of jurisprudence; To add to this aspect, in this scientific paper the researcher revealed method of authorship Imam alMawardi, and showed his general features mentioned by the author in the foreword to his book, which could be developed through the analysis of his book, as well as the features of the alMawardi curriculum of doctrinal research, which the researcher concluded with the most important results of the research, namely: The emergence of the character of Imam alMawardi in his book, his intellectual independence, his remoteness from the doctrinal stalemate, knowledge and the status of the Al-Hawi book among the people of jurisprudence; For its distinctive editing of jurisprudence in a comprehensive and unique manner and outstanding scientific investigation.